2005
DOI: 10.1108/00220410510577989
|View full text |Cite
|
Sign up to set email alerts
|

Critical realism as a philosophy and social theory in information science?

Abstract: PurposeThe philosophical position known as critical realism is briefly introduced, and some of its central features are used to connect the philosophy and the realist social theory to some current library and information science (LIS) models of information behaviour.Design/methodology/approachThe paper uses a literature‐based analysis of the critical realism concepts of a stratified social reality, the importance of contextualisation, and the relation between structure and agency. These features are discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 19 publications
0
41
0
1
Order By: Relevance
“…In seeking to understand the contextual factors that influence information behavior the research not only seeks to observe and interpret, but also seeks to understand cause and relation, in pursuit of changes in management action and policies (Delanty, 2005, p. 147;Wikgren, 2005). However, the researchers also recognize that they need to be alert to their own assumptions, and their funders' motives in intervention and change.…”
Section: Research Philosophymentioning
confidence: 97%
See 1 more Smart Citation
“…In seeking to understand the contextual factors that influence information behavior the research not only seeks to observe and interpret, but also seeks to understand cause and relation, in pursuit of changes in management action and policies (Delanty, 2005, p. 147;Wikgren, 2005). However, the researchers also recognize that they need to be alert to their own assumptions, and their funders' motives in intervention and change.…”
Section: Research Philosophymentioning
confidence: 97%
“…Realism, in contrast to constructivism, emphasizes that realities underlying knowledge do exist, and attempts to integrate three methodologies: the possibility of a causal explanation, the communicative construction of social reality, and the critical dimension (Delanty, 2005, p. 145). Wikgren (2005) suggests that critical realism could be applied to models of information behavior. It is not enough to observe and interpret, perhaps, but to understand some causes and relations, and then to make changes.…”
Section: Information Behavior Models and Research Philosophiesmentioning
confidence: 98%
“…But at the same time, they accepted bureaucracy and regulation as a normal feature of a cooperative, giving the impression the criticism is also a bit of a ritual. Established structures often come with routinized interaction patterns, demonstrating again the entanglement of materialized arrangements and actors' deep insertion in its schedules (Archer 1995;Wikgren 2005;Rolston 2013). …”
Section: At the Asobal Officesmentioning
confidence: 99%
“…The literature review revealed that there were library science theories that have not comprehensively articulated the impact of the current information environment on libraries. Examples include the probability theory (Bensman 2007), the grounded theory (Glaser & Strauss 1967), the grand unified theory (McGrath 2002), the critical realism theory (Wikgren 2005) and the fuzzy set theory (Zadeh 1965). …”
Section: Literature Reviewmentioning
confidence: 99%